2004
DOI: 10.1002/glia.20065
|View full text |Cite
|
Sign up to set email alerts
|

ZnT‐1 expression in astroglial cells protects against zinc toxicity and slows the accumulation of intracellular zinc

Abstract: Zinc ions are emerging as an important factor in the etiology of neurodegenerative disorders and in brain damage resulting from ischemia or seizure activity. High intracellular levels of zinc are toxic not only to neurons but also to astrocytes, the major population of glial cells in the brain. In the present study, the role of ZnT-1 in reducing zinc-dependent cell damage in astrocytes was assessed. Zinc-dependent cell damage was apparent within 2 h of exposure to zinc, and occurred within a narrow range of ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
76
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 102 publications
(82 citation statements)
references
References 44 publications
(67 reference statements)
5
76
0
1
Order By: Relevance
“…ZnTs are known to localize at distinct subcellular compartments, depending on their function as well as their tissue-specific expression pattern (6,33). ZnT1 is predominantly localized at the PM, and it displays a major role as a zinc exporter that protects cells from zinc toxicity (6,34). ZnT3 was shown to localize at synaptic vesicles (20), whereas ZnT2 and ZnT4 have been shown to reside in the membrane of intracellular vesicles/granules, including lysosomes and endosomes (6,26,35), and in a small fraction of cells in the PM (36).…”
Section: Discussionmentioning
confidence: 99%
“…ZnTs are known to localize at distinct subcellular compartments, depending on their function as well as their tissue-specific expression pattern (6,33). ZnT1 is predominantly localized at the PM, and it displays a major role as a zinc exporter that protects cells from zinc toxicity (6,34). ZnT3 was shown to localize at synaptic vesicles (20), whereas ZnT2 and ZnT4 have been shown to reside in the membrane of intracellular vesicles/granules, including lysosomes and endosomes (6,26,35), and in a small fraction of cells in the PM (36).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that ZnT-1 is an endogenous negative regulator of the LTCC (30,31), particularly in the heart, where it appears to participate in cardiac electrical remodeling following atrial fibrillation (31), and in the brain, where it may affect synaptic release (37,40). Nevertheless, the mechanism underlying ZnT-1-induced inhibition of the LTCC has yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…This transmembrane protein has been investigated mainly in the context of zinc metabolism and has been shown to confer resistance to zinc toxicity (32)(33)(34)(35)(36). ZnT-1 is expressed in most tissues, with high levels of expression observed primarily in the brain, the pancreas, the testes, and the heart (37)(38)(39). ZnT-1 inhibition of LTCC activity has recently been confirmed in several cell types (30,31,40).…”
mentioning
confidence: 99%
“…Unlike MT, changes in ZnT1 mRNA and protein expression in preconditioned neurons have not been extensively investigated. However, a conceptually similar investigation has been performed in astrocytes (85). In these cells, sublethal exogenous Zn 2þ exposure induced ZnT1 protein expression and conferred resistance to subsequent lethal Zn 2þ toxicity (85).…”
Section: Preconditioning Triggers Zinc-regulated Gene Expressionmentioning
confidence: 99%
“…However, a conceptually similar investigation has been performed in astrocytes (85). In these cells, sublethal exogenous Zn 2þ exposure induced ZnT1 protein expression and conferred resistance to subsequent lethal Zn 2þ toxicity (85). Further, in nonpreconditioned astrocytes, heterologous expression of ZnT1 reduced toxic intracellular Zn 2þ accumulations and induced Zn 2þ -tolerance (85).…”
Section: Preconditioning Triggers Zinc-regulated Gene Expressionmentioning
confidence: 99%